2014
DOI: 10.5194/acp-14-11221-2014
|View full text |Cite
|
Sign up to set email alerts
|

Aerosol microphysics simulations of the Mt.~Pinatubo eruption with the UM-UKCA composition-climate model

Abstract: Abstract. We use a stratosphere-troposphere compositionclimate model with interactive sulfur chemistry and aerosol microphysics, to investigate the effect of the 1991 Mount Pinatubo eruption on stratospheric aerosol properties. Satellite measurements indicate that shortly after the eruption, between 14 and 23 Tg of SO 2 (7 to 11.5 Tg of sulfur) was present in the tropical stratosphere. Best estimates of the peak global stratospheric aerosol burden are in the range 19 to 26 Tg, or 3.7 to 6.7 Tg of sulfur assumi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
144
1

Year Published

2015
2015
2016
2016

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 83 publications
(156 citation statements)
references
References 103 publications
(146 reference statements)
11
144
1
Order By: Relevance
“…There are several previous global model studies that where evolution of stratospheric aerosols following Pinatubo eruption has been investigated. Many of these shows similar sulfate burden than in the our study and overestimation of sulfate burden compared to the HIRS data English et al, 2012;Dhomse et al, 2014;Sheng et al, 2015). This comparison between the limited set of the observational data and with other modelling studies gives us confidence that the new MAECHAM5-HAM-SALSA set-up simulates aerosol loads and properties consistent to observations under high stratospheric sulfur conditions.…”
Section: Microphysical Simulations Of Volcanic Eruption and Srm Compasupporting
confidence: 49%
“…There are several previous global model studies that where evolution of stratospheric aerosols following Pinatubo eruption has been investigated. Many of these shows similar sulfate burden than in the our study and overestimation of sulfate burden compared to the HIRS data English et al, 2012;Dhomse et al, 2014;Sheng et al, 2015). This comparison between the limited set of the observational data and with other modelling studies gives us confidence that the new MAECHAM5-HAM-SALSA set-up simulates aerosol loads and properties consistent to observations under high stratospheric sulfur conditions.…”
Section: Microphysical Simulations Of Volcanic Eruption and Srm Compasupporting
confidence: 49%
“…Although this study is focused on the upper stratosphere, we can note that there is significant reduction in the lower stratospheric SCS in all the simulations, as the effect of volcanic aerosol on estimation of SCS is less than 2% in our present simulations due to improvements in simulating chemical ozone changes after the volcanic eruption . However, it is also important to note that radiative heating and subsequent changes in Brewer-Dobson (BD) circulation are probably not well simulated in ERA-Int due to the lack of a detailed aerosol microphysics module [e.g., Dhomse et al, 2014] in the European Centre for Medium-Range Weather Forecasts reanalysis system.…”
Section: 1002/2016gl069958mentioning
confidence: 99%
“…A recent study of the Pinatubo eruption (Dhomse et al 2014) showed that the satellite-observed post-eruption increase in mid-visible aerosol optical depth is consistent with a considerably lower mass of sulfuric acid in the aerosol when variations in particle size are simulated. The study also emphasized that satellite estimates of the peak global sulfur burden in the particles are around 50% lower than the measured gas phase sulfur burden shortly after the eruption.…”
Section: Climate Models With Interactive Stratospheric Aerosolmentioning
confidence: 99%
“…Niemeier et al 2009;Dhomse et al 2014). Many of these models also include aerosol microphysical modules to calculate sedimentation rates and aerosol-radiation interactions consistently with simulated global variations in particle size distribution.…”
Section: Climate Models With Interactive Stratospheric Aerosolmentioning
confidence: 99%
See 1 more Smart Citation